Concentration and integrity index of circulating cell-free DNA as a biomarker in pediatric patients with B-ALL: ccf-DNA as biomarker in pediatric B-ALL patients - Rodriguez-Ortiz, Jessica Fabiola; Saucedo-Sariñana, Anilú Margarita; Rosales-Reynoso, Mónica Alejandra; Soto Padilla, Janet; Ortíz-López, Rocío; Jaloma-Cruz, Ana Rebeca; Tovar-Jácome, César de Jesús; Barros-Núñez, Patricio (Cellular and Molecular Biology, 2025)
The objective of this study was to evaluate the concentration and integrity index of circulating cell-free DNA (ccf-DNA) as biomarkers for the detection and monitoring of minimal residual disease (MRD) in pediatric patients with B-cell acute lymphoblastic leukemia (B-ALL). Comparison with a validated methodology for the quantification of monoclonal rearrangements of the IGH gene was made. Peripheral blood and bone marrow samples were collected from 10 pediatric patients with B-ALL at diagnosis, remission, and maintenance phases. Total ccf-DNA concentration was estimated using Qubit® fluorometry, and the integrity index was obtained through qPCR amplification of ALU247/ALU115 fragments. Monoclonal rearrangements of the IGH gene were quantified by multiplex PCR and detected by capillary electrophoresis. Results showed that at diagnosis, the mean ccf-DNA concentration was 5,607 ng/mL with an integrity index of 0.38; during remission induction, they were 968 ng/mL and 0.35; and during the maintenance phase, 748 ng/mL and 0.33, respectively. Differences between treatment phases were significant (p=0.02). The reference group had a mean ccf-DNA concentration of 247 ng/mL and an integrity index of 0.20, showing significant differences compared to the patient group (p=0.01). Monoclonality analysis showed significant differences between diagnosis and remission (p=0.022) and between diagnosis and maintenance (p=0.001). Linear regression analysis during treatment demonstrated a similar trend for ccf-DNA concentration and monoclonality. In conclusion, ccf-DNA concentration and integrity index could be useful biomarkers for monitoring MRD in patients with B-ALL, showing comparable efficacy to the detection of monoclonality in the IGH gene.